Damage-mediated macrophage polarization in sterile inflammation - Koncz, Gábor; Jenei, Viktória; Tóth, Márta; Váradi, Eszter; Kardos, Balázs; Bácsi, Attila; Mázló, Anett (Frontiers in Immunology, 2023)
Most of the leading causes of death, such as cardiovascular diseases, cancer, dementia, neurodegenerative diseases, and many more, are associated with sterile inflammation, either as a cause or a consequence of these conditions. The ability to control the progression of inflammation toward tissue resolution before it becomes chronic holds significant clinical potential. During sterile inflammation, the initiation of inflammation occurs through damage-associated molecular patterns (DAMPs) in the absence of pathogen-associated molecules. Macrophages, which are primarily localized in the tissue, play a pivotal role in sensing DAMPs. Furthermore, macrophages can also detect and respond to resolution-associated molecular patterns (RAMPs) and specific pro-resolving mediators (SPMs) during sterile inflammation. Macrophages, being highly adaptable cells, are particularly influenced by changes in the microenvironment. In response to the tissue environment, monocytes, pro-inflammatory macrophages, and pro-resolution macrophages can modulate their differentiation state. Ultimately, DAMP and RAMP-primed macrophages, depending on the predominant subpopulation, regulate the balance between inflammatory and resolving processes. While sterile injury and pathogen-induced reactions may have distinct effects on macrophages, most studies have focused on macrophage responses induced by pathogens. In this review, which emphasizes available human data, we illustrate how macrophages sense these mediators by examining the expression of receptors for DAMPs, RAMPs, and SPMs. We also delve into the signaling pathways induced by DAMPs, RAMPs, and SPMs, which primarily contribute to the regulation of macrophage differentiation from a pro-inflammatory to a pro-resolution phenotype. Understanding the regulatory mechanisms behind the transition between macrophage subtypes can offer insights into manipulating the transition from inflammation to resolution in sterile inflammatory diseases.